Analisis Strategi Operasional dan Tata Kelola Sanitasi Publik: Studi Kasus Revitalisasi Pasar Wosi Manokwari - Maria Magdalena Semet; Sisilia Maria Parinusa; Siti Aisyah Bauw (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Traditional market sanitation is a critical aspect of environmental health and food safety, as markets operate as public spaces with high activity levels and significant waste generation. This study aims to assess the sanitation conditions of Wosi Market in Manokwari based on environmental health standards and to formulate sustainable sanitation management strategies. A qualitative descriptive approach was applied, with data collected through field observations, semi-structured interviews, and documentation. Sanitation conditions were evaluated using a descriptive-comparative analysis with a Guttman scale covering eight sanitation indicators in accordance with Indonesian Ministry of Health Regulations No. 17 of 2011 and No. 32 of 2017. The results indicate that Wosi Market exhibits very poor sanitation conditions, with a 0% compliance rate, meaning none of the indicators met the required standards. This condition is caused by inadequate sanitation infrastructure, weak market management, and low hygiene awareness among traders and visitors. SWOT analysis was used to formulate sanitation management strategies, emphasizing infrastructure revitalization, strengthened management and regulation, and continuous hygiene education. This study provides policy-relevant insights for improving sanitation management in traditional markets.